1973
DOI: 10.1111/j.1365-2818.1973.tb03799.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced contrast in electron microscopy of unstained biological material

Abstract: In-focus phase contrast electron microscopy has been investigated for the enhancement of bulk contrast (i.e. the contrast of large regions) of model biological specimens. Carbon film phase plates, of measured thickness, were introduced into the back focal plane ofthe objective lens. Image contrast was determined from Faraday-cage intensity measurements. A contrast enhancement was observed but was measured to be less than that obtained using a very small objective aperture. This was attributed to the smaller pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…As was anticipated, dark field gave very poor resolution and contrast on thick specimen areas (Johnson & Parsons, 1969) but improved contrast and equal resolution for thin areas. This can be seen in Fig.…”
Section: (7) Imaging Modementioning
confidence: 53%
“…As was anticipated, dark field gave very poor resolution and contrast on thick specimen areas (Johnson & Parsons, 1969) but improved contrast and equal resolution for thin areas. This can be seen in Fig.…”
Section: (7) Imaging Modementioning
confidence: 53%
“…for very thin specimens) that dark-field image formation produces high contrast. Numerical data obtained from theoretical and practical measurements (Hall, 1951;Johnson & Parsons, 1969) showed that this plateau is situated in the region of 40-60 nm gm/cm3 for an acceleration voltage in the order of 100 kV. This mass thickness includes the supporting film.…”
Section: S P E C I M E N P R E P '4 R a T I0 Nmentioning
confidence: 92%
“…( 2 ) Theoretical study (a) Di'erence from strioscopy. The contrast-stop method is often called strioscopy (Johnson & Parsons, 1969). Such a term may suggest wrong analogies.…”
Section: R I T I C a L S T U D Y O F T H E C O N T R A S T -S T O Pmentioning
confidence: 99%